(untitled) (Bangladesh Journal of Botany, 2021)
An experiment was conducted during 2013 -2019 to study the impact of intergrated nutrient management through organic matter recycling (OMR) on the soil properties, leaf nutrient status and yield of coconut and its components crops at Regional Coconut Research Station (AICRP on Palms), Bhatye, Maharashtra, India. The experiment was laid out in 0.40 ha with four treatments namely T1, T2, T3 and T4. Results showed that, INM practices significantly improved the soil physico-chemical, biological properties and leaf nutrient status, whereas it was more prominent for the T1 treatment. The soil organic carbon content during post experimental period gradually increased in the organic recyclable treatment under cropping system (0.80 to 0.86%) compared to monocropping (0.60%). The recyclable biomass produced from the system varied between 9.0 - 18.0 t/ha/year and vermicompost produced was 4.8 to 10.2 t/ha/year by composting through earthworm. The nut yield (147.2 and 138.4 nuts/palm), copra output (25.75 and 23.06 kg/palm) and oil output (17.11 and 15.72 kg/palm) under treatment T1 and T2 were on par and differed significantly compared to monocrop. Bangladesh J. Bot. 50(4): 1067-1075, 2021 (December)